An analysis of energy production and efficiency in various longbow archery models longbow archery models - McPherson, H. (BC Digital Commons, Senior Honors Projects, Bridgewater College,, 2022)
An analysis of the energy production and efficiency of three lab-tested longbow models is undertaken. The first model, which is constructed to not allow flexing of limbs and which uses a frictionless cart and track in place of an arrow, demonstrated an efficiency of 50% +/- 40%. The second model, which is constructed similarly to the first with the exception of a wooden dowel now being used as an arrow-like object, demonstrated an efficiency of 13% +/- 3%. The last model, a 3D printed longbow with flexible limbs using the wooden dowel as an arrow-like object, demonstrated an efficiency of 40% +/- 10%. A conclusion that may be drawn from this data, as well as from the values of work and kinetic energy contained herein, is that the flexibility of the limbs increases the energy efficiency of the bow. The results from the second and third models in particular, may explain how the flexible limbs of a real longbow facilitate the transfer of stored energy directly into kinetic energy, lowering the total amount of energy lost through other forms, such as vibrational in the strings.